Rapid rates of newly synthesized mitochondrial protein degradation are significantly affected by the generation of mitochondrial free radicals. - Basoah, A; Matthews, P; Morten, K (2005)
Exposure of biological material to high levels of free radicals causes extensive cellular damage. Reactive oxygen species (ROS) generated by mitochondria have been associated with a variety of diseases and aging. We investigated the effect of low-level mitochondrial ROS production on newly synthesized mitochondrial proteins which are potentially vulnerable to mitochondrial ROS due to their location and unfolded state. We show that elevated mitochondrial ROS increases the degradation of newly synthesized mitochondrial proteins with some proteins more sensitive than others. In the long term reduced assembly of mitochondrial complexes would affect mitochondrial function and may trigger a vicious cycle of mitochondrial ROS production.